Clinical characteristics, laboratory findings, radiographic signs and outcomes of 61, 742 patients with confirmed COVID-19 infection: A systematic review and meta-analysis. (October 2020) - Pormohammad, Ali; Ghorbani, Saied; Baradaran, Behzad; Khatami, Alireza; J. Turner, Raymond; Mansournia, Mohammad Ali; Kyriacou, Demetrios N.; Idrovo, Juan-Pablo; Bahr, Nathan C.
Abstract: Introduction: In the current time where we face a COVID-19 pandemic, there is no vaccine or effective treatment at this time. Therefore, the prevention of COVID-19 and the rapid diagnosis of infected patients is crucial. Method: We searched all relevant literature published up to February 28, 2020. We used Random-effect models to analyze the appropriateness of the pooled results. Result: Eighty studies were included in the meta-analysis, including 61, 742 patients with confirmed COVID-19 infection. 62.5% (95% CI 54.5–79, p < 0.001) of patients had a history of recent travel endemic area or contact with them. The most common symptoms among COVID-19 infected patients were fever 87% (95% CI 73–93, p < 0.001), and cough 68% (95% CI 55.5–74, p < 0.001)), respectively. The laboratory analysis showed that thrombocytosis was present in 61% (95% CI 41–78, p < 0.001) CRP was elevated in 79% (95% CI 65–91, p < 0.001), and lymphopenia in 57.5% (95% CI 42–79, p < 0.001). The most common radiographic signs were bilateral involvement in 81% (95% CI 62.5–87, p < 0.001), consolidation in 73.5% (95% CI 50.5–91, p < 0.001), and ground-glass opacity 73.5% (95% CI 40–90, p < 0.001) of patients. Case fatality rate (CFR) in <15 years old was 0.6%, in >50 years old was 39.5%, and in all range group was 6%. Conclusions: Fever and cough are the most common symptoms of COVID-19 infection in the literature published to date. Thombocytosis, lymphopenia, and increased CRP were common lab findings although most patients included in the overall analysis did not have laboratory values reported. Among Chinese patients with COVID-19, rates of hospitalization, critical condition, and hospitalization were high in this study, but these findings may be biased by reporting only confirmed cases. Highlights: Eighty studies (61, 742 patients) with confirmed COVID-19 infection included in this study. Bilateral involvement (81%), consolidation (73.5%), and ground-glass opacity (73.5%) was most common radiographic signs. Case fatality rate (CFR) in <15 years old age group was 0.6%, in >50 years old was 39.5%, and in all range group was 6%.